Effect of molecular carbon structures on the evolution of the pores and strength of lignite briquette coal with different heating rates. (1st January 2022) - Gan, Qingqing; Xu, Jiang; Peng, Shoujian; Yan, Fazhi; Wang, Ruifang; Cai, Guoliang
Highlights: The micropores of BC-5 ℃/min was greater than other BC. The mechanical strength of BC-5 ℃/min was close to RC. Heating rate primarily affects the longitudinal conjugation and condensation of the briquette. The aromatic rings gradually shortened, and their aromaticity values increased with increase in the heating rate. Abstract: Briquette coal (BC) is the material produced from coal and gas outburst experiments. Preparing BC via the heating and pressure method can improve its low mechanical strength in physical simulation tests and gas outbursts while increasing experimental reliability. However, the influence of heating rate on the mechanical properties and microstructure of BC and the reasons underlying the evolution of its mechanical strength analyzed in terms of carbon molecular structure still need to be further studied. In this study, we developed an experimental system to prepare BC. The influence of the pore and carbon molecular structure on the BC uniaxial compressive strength was examined via a rock mechanics test system, scanning electron microscopy, nuclear magnetic resonance, specific surface area analysis, X-ray diffraction, and Fourier transform infrared spectroscopy. The results indicated that when the heating rate was increased from 3 to 6 °C/min, the briquette structure changed from looser smooth sheets to rough agglomerates of coal. The pore types observed after four different heating treatments (3, 4, 5, and 6 °C/min) on briquette samples were primarily micropores and mesopores. At 5 ℃/min, the number of micropores in the briquette sample were significantly higher than that observed in other samples. All samples exhibited similar adsorption curves as those of inverted "S"-type coal samples, which can be regarded as a combination of Type IV isotherms. With increasing heating rates, the La and Lc first increased and then decreased, with a decrease in Aar /Aal, whereas Hal /H and CH2 /CH3 increased. The strength of coal samples under the increasing heating rates were 5.62, 6.43, 7.07, and 5.99 MPa, respectively. The heating rate of 5 ℃/min was found to be the appropriate heating rate for briquette preparation. These results can provide an excellent alternative raw material required for large-scale physical simulation experiments for the prevention and control of coal and gas outbursts.